Iskanje izgubljenega govora - Žemva, Nada (Rehabilitacija (Ljubljana), 2009)
The article reviews aphasia rehabilitation predominantly in the English speaking world and aphasia treatment in Slovenia. Advances in neuroscience have already had an important impact on speech and language rehabilitation. It is expected that this impact will grow in the future. The International Classification of Functioning, Disability and Health (ICF) has changed the attitude towards planning and practice of aphasia rehabilitation. Social consequences of aphasia have been accentuated growingly. In the future, much is expected from new technologies such as internet, distance learning and virtual clinicians.
Keywords: govorne motnje; govor; afazija; rehabilitacija; vocational rehabilitation